Profound peripheral T-lymphocyte depletion and activation in disseminated tuberculosis - Denise Silva Rodrigues (Brazilian Journal of Infectious Diseases)
Three HIV-1-seronegative patients with disseminated tuberculosis presented significant depletion of T-cell counts, in CD4+ and/or CD8+ cells, associated with increased expression of activation marker CD38 on CD8+ T-lymphocytes. This finding raises the question of potential mechanisms involved in the activation or loss of T-cells in disseminated tuberculosis.